EFEKTIVITAS MEDIA MIND MAP BERBASIS METODE LATIHAN BERJENJANG TERHADAP HASIL DAN RETENSI BELAJAR SISWA PADA MATERI KONSEP MOL DI KELAS X SMA NEGERI 8 PONTIANAK - Tesa Puteri Permatasari; Dini Hadiarti; Raudhatul Fadhilah (Jurnal Ilmiah Ar-Razi, 2017)
ABSTRACTThe results and retention of student learning is still low in learning the concept of mole due to the difficulties of students to understand the concept and the lack of ability to resolve the matter of calculation. This study aimed to determine the differences in the results and retention of learning between the students who were taught with and without using mind-map media based on tier training method in the material of mole concept, knowing the great effectiveness of mind-map media based tier training method toward the results and retention of students in the material of mole concept at X grade students of SMAN 8 Pontianak. This research used Quasi Experimental Research with control group design. This research used purposive sampling with X MIA 4 as the experimental class and X MIA 3 as the control class. The techniques of collecting data used measurement techniques, observation and interviews, while the data collection tools used the test results and retention of learning, observation sheet and questionnaire. Mann-Whitney U test as the data analysis showed that there were some differences in learning while the t-test showed that there were differences in retention of learning. The results of the data showed that there were differences in learning outcomes and retention between the students who were taught with and without mindmap media based on tiered training method. Learning by using mind-map media gave effectiveness to the result of students learning outcomes which 24,86% categorized as medium category, the retention of student learning for 8 days was 28,52% categorized as medium category.Keywords: learning outcomes, tier training method, mind-map, retention